A study on usage of knowledge management tools in Singapore. - Lee, Ling. (2008)
This research identifies that organizational culture is the only organizational factor that determines the successful implementation of KM tools, and IT firm are found to be more sucessful in the implementation of KM tools compared to non-IT firms.